Advances in osteobiologic materials for bone substitutes. (21st May 2018) - Hasan, Anwarul; Byambaa, Batzaya; Morshed, Mahboob; Cheikh, Mohammad Ibrahim; Shakoor, Rana Abdul; Mustafy, Tanvir; Marei, Hany E.
Abstract: A significant challenge in the current orthopedics is the development of suitable osteobiologic materials that can replace the conventional allografts, autografts, and xenografts and thereby serve as implant materials as bone substitutes for bone repair or remodelling. The complex biology behind the nanostructure and microstructure of bones and their repair mechanisms, which involve various types of chemical and biomechanical signalling amongst different cells, has set strong requirements for biomaterials to be used in bone tissue engineering. This review presents an overview of various types of osteobiologic materials to facilitate the formation of the functional bone tissue and healing of the bone, covering metallic, ceramic, polymeric, and cell‐based graft substitutes, as well as some biomolecular strategies including stem cells, extracellular matrices, growth factors, and gene therapies. Advantages and disadvantages of each type, particularly from the perspective of osteoinductive and osteoconductive capabilities, are discussed. Although the numerous challenges of bone regeneration in tissue engineering and regenerative medicine are yet to be entirely addressed, further advancements in osteobiologic materials will pave the way towards engineering fully functional bone replacement grafts.